Process evaluation of a hybrid effectiveness-implementation, pragmatic, cluster randomised controlled trial (IMPULSE) to improve psychosocial treatment of patients with psychotic-spectrum disorders in Southeast Europe - Tamara Pemovska; Nikolina Jovanović; Tamara Radojičić; Silvana Markovska Simoska; Fjolla Ramadani; Sanja Andrić Petrović; Emina Karamehić; Biljana Blazhevska Stoilkovska; Jon Konjufca; Stefan Jerotić; Alma Džubur Kulenović; Lidija Injac Stevović; et al. (PLoS ONE, 2026)
Background The IMPULSE trial investigated the effectiveness and implementation of a digital psychosocial intervention (DIALOG+) for people with psychosis in five Southeast European countries. DIALOG+ significantly improved patients’ quality of life after four treatment sessions. The process evaluation reported here aimed to assess contextual influences on intervention delivery during the trial, to explain the trial findings and generate hypotheses about mechanisms of action by exploring acceptability from the perspectives of clinicians who delivered it and trial participants who received it, and fidelity (was the intervention delivered and received as planned?). Method A mixed-methods process evaluation was conducted in accordance with the published protocol, guided by theoretical frameworks and the Medical Research Council’s guidance for complex interventions. To explore the role of context, data were analysed about the participating services, policy documents, and from focus groups with key stakeholders. Semi-structured interviews with clinicians and patients were conducted to explore acceptability. Process data (format and content of sessions) were analysed to assess intervention fidelity. Data analysis included descriptive methods, framework and content analysis, and triangulation. Results Several attributes of context related to health services, including resource limitations, funding priorities, reliance on paper records and lack of community support, potentially negatively impacted DIALOG+ acceptability, fidelity and outcomes. Contextual enablers were also identified, including an appetite for change among key stakeholders that can help overcome contextual barriers. Acceptability of the psychosocial intervention was moderate to high and fidelity was high. Conclusions Intervention acceptability is likely to have played a key role in ensuring high fidelity, which in turn likely contributed to the intervention’s positive impact on patients’ quality of life. The high fidelity confirms that the IMPULSE trial findings provide a valid assessment of the intervention as designed. While the identified contextual barriers appear not to have impaired intervention fidelity, acceptability and outcomes, they could pose challenges to the long-term sustainability of the intervention. Trial registration Retrospectively registered on 29 March 2021, ISRCTN11913964